Facts, causes and corruption prevention: Evidence in Indonesian ministries - Arismaya, Anisa; Utami, Intiyas (Master in Accounting Program, Faculty of Business & Economics, Universitas Islam Indonesia, Yogyakarta, Indonesia, 2019)
This study aims to track corruption cases and describe the causes of corruption in the Indonesian ministry in 2016, 2017, 2018 using descriptive analysis. Data on corruption cases is taken from Indonesian online media news. Furthermore, identifying the level of implementation of the violation reporting system in the Indonesian ministry by using content analysis from the whistleblowing system website in 21 ministries in Indonesia using categorical items from the whistleblowing system implementation according to the KNKG 2008. The results of the study showed that 21 Indonesian ministries applied 19.84 % of the reporting system which means it is in accordance with the reporting system criteria in accordance with the 2008 KNKG. This research will be input for the Indonesian ministry in implementing the reporting system and contribute in the field of accounting as a fraud prevention tool. This research update is carried out by conducting studies for each ministry in Indonesia that has a whistleblowing system website.